Penerimaan Audiens di Kota Surabaya Terhadap Representasi Toxic Relationship Pada Konten #Closethedoor Episode Clara Tan - Permata, Permata Aulia Rosul; Claretta, Dyva (Unitri Press, 2024)
Nowadays, there are many toxic dating relationships that threaten people's lives. This is no exception experienced by Clara Tan, an accomplished model who was a victim of a toxic relationship and then ventured to speak up in the media, one of which was on the Close the Door Podcast. This research aims to analyze the acceptance of audiences in Surabaya City towards the representation of toxic relationships in the content of #CLOSETHEDOOR “Toxic Relationship Tortured Me!!! Clara Tan, ANTM Model Speak Up”. The research method uses a descriptive qualitative approach with data collection in the form of in-depth interviews and documentation. The findings of this study indicate that the reception of Clara Tan's podcast content on Close the Door varies among audiences interpreting toxic relationships. There are 3 (three) audiences agreed that through the close the door podcast content, victims of toxic relationships must dare to speak up, not give space, and dare to say 'no' to actions that lead to toxic. Meanwhile, 2 (two) audiences assessed that the content of this podcast reminds women to be able to take precautions as early as possible before being in a phase of experiencing violence that threatens mental and physical. Abstrak Saat ini marak terjadi hubungan berpacaran yang toxic hingga mengancam nyawa manusia. Hal ini tak terkecuali dialami oleh Clara Tan seorang model berprestasi yang menjadi korban toxic relationship dan kemudian memberanikan diri untuk speak up di media, salah satunya pada Podcast Close the Door. Penelitian ini bertujuan untuk menganalisis penerimaan audiens di Kota Surabaya terhadap representasi toxic relationship pada konten #CLOSETHEDOOR “Toxic Relationship Di Siksa Saya Habis2an!! Clara Tan, Model ANTM Speak Up”. Metode penelitian menggunakan pendekatan deskriptif kualitatif dengan pengumpulan data berupa wawancara mendalam dan dokumentasi. Temuan penelitian ini menghasilkan bahwa resepsi pada konten podcast Clara Tan di Close the Door berbeda-beda di antara para audiens memaknai toxic relationship. Terdapat 3 (tiga) audiens menyepakati bahwa melalui konten podcast close the door, korban toxic relationship harus berani untuk dare to speak up, tidak memberikan ruang, dan berani berkata ‘tidak’ terhadap tindakan yang mengarah pada toxic. Sedangkan 2 (dua) audiens menilai konten podcast ini mengingatkan untuk perempuan agar mampu melakukan pencegahan sedini mungkin sebelum berada fase mengalami kekerasan yang mengancam mental dan fisik.